A model of the anisotropic distribution of microvascular volume in the periodontal ligament of the mouse mandibular molar - Sims Milton R. (Sciendo, 1987)
Histological sections of periodontal ligament from the mesial root of ten randomly selected mouse mandibular molars were digitised for luminal vascular volume. Total vascularity differed markedly between mice. Statistical analysis, using a logistic model, revealed significant quadrant and depth effects at the 1 percent level with regional vascular volumes varying from 3 to 35 percent. Maximum vascular volume occurred in the lingual quadrants and minimum volume characterised the buccal quadrants. Depth effects were maximal at the apical limit and minimal in the mid root regions, whereas the cervical ligament had a vascular volume midway between the other two regions. The overall average for the vascular volume was 10.9 per cent. This ligament model demonstrates marked volumetric gradients in distribution of the microvascular bed.